Gender Differences of Vocabulary Size: A Study on Bilingual Classes of SMP Islam Raudhatul Jannah Payakumbuh - Fatimmessiah Azzuhrah; M. Zaim (Universitas Negeri Padang, 2023)
This study aims to find the gender differences of vocabulary size of bilingual classroom’s students in SMP Islam Raudhatul Jannah Payakumbuh. This study used quantitative approach with descriptive-comparative design. The participants of this study were 94 students of bilingual class in SMP Islam Raudhatul Jannah Payakumbuh. The samples were chosen using purposive sampling. The data were collected using New Vocabulary Levels Test to measure the students’ vocabulary size. It was found that the vocabulary size of male students grade 7th, 8th and 9th were 2518.93 words, 3371.21 words, and 3381.94 words. While female students’ vocabulary size fore grade 7th, 8th, and 9th were 2468.25 words, 2898.80 words, and 3842.59 words. There were no statistical significant differences found between the mean vocabulary size of male and female students grade 7th and 8th. The significant difference was found in vocabulary size difference of male and female students’ in grade 9th. It can be concluded that the vocabulary size of male and female students’ were different and increased along with their educational level. The significant difference of vocabulary size between male and female students was only found in grade 9th where female students possessed a bigger number of vocabulary size compared male students.